Distribution of the genus Sparus (Perciforme: Sparidae) in the Terciary of Western Cuba - Viñola-López, Lázaro W. (2016)
Osteichthyans fossil remains are common into the Tertiary of Cuba, in spite of its abundance, few studies have treatise them. In this study, we report for the first time for the Great Antilles two species of the genus Sparus (S. cinctus Agassiz, 1843 and S. neogenus Aramboug, 1927) proceedings of ten localities of western Cuba. Beside, some paleoenvironmental and taphonomical inferences, based on the taxa are made.